Baseline design of laser fusion research reactor with MW class laser facility - Akifumi Iwamoto; Masahiro Tanaka; Keisuke Shigemori; Ryosuke Kodama (Nuclear Fusion, 2024)
We propose a sub-ignition/burning reactor which is named the Laser-fusion Subcritical Power Reactor Engineering Method (L-Supreme). The reliabilities of L-Supreme in a MW class laser facility are assessed with respect to the following points: a reactor core, a target chamber, a target delivery system, an Exhaust Detritiation System (EDS), and neutron shielding. The Japan Establishment for Power-laser Community Harvest (J-EPoCH) would be applied as a MW class laser facility. A non-cryogenic glass balloon target filled with gaseous deuterium-tritium (DT) is contained in a target capsule. A chain-type magazine system might be used for a mass supply of the target capsules. Each target capsule is delivered to the center of a reactor core at 1 Hz. A batch of 10 000 laser shots would realize 0.22 MJ fusion power. The amount of tritium per batch is 1.51 × 10 ^12 Bq. During laser experiments, unburned tritium is evacuated and transferred into an Exhaust Detritiation System (EDS). An evacuation rate of more than 0.1 m ^3 s ^−1 is required in order to recover less than 5000 Bq m ^−3 of the threshold of tritium concentration within 1 h. For safety, emergency situations such as tritium leakage in facilities are examined. The EDS works by internal circulation processes. Assuming leakage of tritium for a batch, an air circulation flow rate of 4100 Nm ^3 h ^−1 is required in an experimental hall for recovering less than 5000 Bq m ^−3 within 48 h. A primary and secondary neutron shield concept are proposed and would provide full neutron shielding. We conclude that it is possible to construct the L-Supreme system by marshalling current technologies.